Effect of Ce doping on microstructural, morphological and optical properties of ZrO2 nanoparticles. (February 2015) - Gnanamoorthi, K.; Balakrishnan, M.; Mariappan, R.; Ranjith Kumar, E.
Abstract: Pure and Ce doped ZrO2 nanostructures have been synthesized by the microwave irradiation method. The prepared nanoparticles were characterized by various analytical techniques like Thermogravimetric and Differential Thermal Analysis (TG–DTA), X-Ray Diffraction (XRD), Fourier Transform Infra-Red Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Energy Dispersive Spectrum (EDS) and Transmission Electron Microscopy (TEM). The XRD pattern of Ce doped ZrO2 nanoparticles have been confirms that the tetragonal structure. TEM observations indicated that the average particle size of the pure ZrO2 some particles spherical shaped and some particles agglomeration in the range of 16–44 nm. Whereas on addition of Ce agglomeration in the range of 32–56 nm. The pure ZrO2 and Ce doped ZrO2 nanoparticles were further characterized for their optical properties by UV–vis reflectance spectra (DRS) and Photoluminescence (PL) spectroscopy.